Shape by Shape - MacDonald, Suse (New York : Little Simon, 2009)
Introduces young readers to shapes, using die-cut pages to reveal gradually parts of an overall picture as the reader is asked to guess what the eventual picture will be.
new kids book 2025 spring.
Keywords: Shape -- Juvenile fiction; Shapes; Picture books; Dinosaurs; Toy and movable books -- Specimens -- Juvenile fiction